A causal model of organic food buying behaviours of consumers in Thailand - Pattweekongka, Supawadee; Napompech, Kulkanya; Chaiyasoonthorn, Wornchanok (My University, 2019)
This quantitative study aims to understand the causal factors of food buying behaviour in the current Thai market for organic food as differentiated by brand marketing. A comprehensive model of consumer decision-making was developed with four latent factors, including trust in brand, buying intention, brand loyalty and buying behaviour. This model demonstrated high reliably measurements as a basic requirement of structural equation modelling (SEM) statistics. Questionnaires were collected from a sample of organic food consumers in Thailand between April and June 2018; 386 data records were obtained and analysed using SEM. A significant correlation was found between the observed data and the conceptual model. The model demonstrated that the effect of brand trust on brand loyalty influenced buying intention, which played a key role in driving buying behaviour. Findings show that "loyalty" was the most important factor to affect "intention," which directly impacted on buying behaviour. Further, the model achieved predictive power at 94%. Results indicate that Thai consumers perceive organic food marketing as distinct, which is reflected in their purchasing behaviours. These findings should benefit organic food entrepreneurs, farmers and sellers who must devise strategies for organic food-related branding.
Keywords: Brand loyalty; Consumer trust; Organic buying behaviour; Organic food; Trust in brand